(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Environment and the living beings are two dynamic and complex segments of nature. Environment directs the life of the life forms including human beings. Dynamic learning is important for the improvement of science and environmental issues since it can in a roundabout way address the social and environmental issues just as environmental effects including the environmental results of human conduct. Environmental awareness among understudies is exceedingly impacted by their experience, information, attitude and affectability towards the environment. The objectives of this examination are to distinguish level of learning on environmental proficiency and attitude towards environmental issues that are happening in our nation.